Comparettia sotoana (Orchidaceae: Oncidiinae), a new Ecuadorian specieS - Pupulin, Franco (2013)
A new species of Comparettia, C. sotoana, is described and illustrated from the province of Morona- Santiago, in southeastern Ecuador. Comparettia sotoana is compared with Comparettia langkastii, from which it mainly differs by the laterally flattened leaves, the subumbellate (vs. distichous), several-flowered (vs. 2-flowered) inflorescence, the short, straight sepaline spur (vs. long, curved), and the ovate-subpandurate lip with a cuspidate midlobe (vs. pandurate with a deeply retuse, apiculate midlobe) provided with digitateconical basal processes, uncinate at apex and expanded into rounded knobs (vs. straight, acuminate), and lacking apical calli (present in C. langkastii).